The Influence Of Information Technology Competence, Human Resource Development Innovation On Work Motivation And Employee Performance At The Department Of Agriculture And Food Security Of The Selayar Islands Regency - Wahyudi, Andi Nurdiansyah; Mappatompo, Andi; Nurbaya, Sitti (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2026)
This study aims to examine and analyze the effect of information technology competence and human resource development innovation on work motivation and employee performance at the Department of Agriculture and Food Security of Selayar Islands Regency. This research employs a quantitative approach. The population of this study consists of all employees of the Department of Agriculture and Food Security of Selayar Islands Regency, totaling 98 employees. The sampling technique used is saturated sampling, in which the entire population is included as respondents. Data were collected using questionnaires as the research instrument. The data analysis technique applied in this study is path analysis, assisted by AMOS software, to examine both direct and indirect effects among variables. The results indicate that information technology competence and human resource development innovation have a positive and significant effect on employee work motivation. Work motivation is also proven to have a positive and significant effect on employee performance. However, information technology competence and human resource development innovation do not have a significant direct effect on employee performance. Furthermore, the findings show that work motivation is able to mediate the effect of information technology competence and human resource development innovation on employee performance. These results suggest that improvements in employee performance are not solely determined by technological mastery and human resource development innovation, but are highly dependent on the role of work motivation as the main driving factor within the organization.